Revisiting the Concept of an Integrated Curriculum and Its Implications for Contemporary Islamic Schools - Rahimah, Embong; Solehah, Yaacob; Wan Mohd Azam, Wan Mohd Amin (2014)
The dilemma and confusion of the Ummah will never end without a clear understanding of the meaning of “integration” and “Islamization of knowledge”. Muslims are still confused and doubtful about the kind of Islamization direction to take. Different scholars differ in their interpretation of the theory of Islamization of knowledge and suggest different approaches and methodologies to it. In order to have a better scenario, the study attempts to address the following set of questions: 1. What are the causes and effects of the bifurcation or dualism in the educational system of the Ummah? 2. What is the nature of the integrated curriculum as perceived by existing contemporary Islamic schools? and 3. What are the implications of revisiting the concept of the integrated curriculum from the Islamic Weltanschauung for contemporary Islamic educational system? In order to elucidate the above questions, the philosophical and historical methodologies as well as analytical study would be employed. Relevant texts, conceptions, and ideas from the three main kinds of sources—primary, secondary, and tertiary sources of literature—will be reviewed and analyzed. As a result, the balance judgment can be made in order to implement the concept.